A single-metallic cobalt MOF-polyacrylonitrile electrospun nanofiber membrane, a preparation method and application thereof

CN122879907APending Publication Date: 2026-10-09ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611166219.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本发明的目的在于解决如何开发兼具高过滤效率与低空气阻力的复合纳米纤维过滤介质的问题,提供了一种单金属钴MOF-聚丙烯腈静电纺丝纳米纤维膜、制备方法及其应用

Benefits of technology

[0019]1、本发明利用金属有机框架(MOFs)材料具有大的比表面积、丰富的金属活性位点和高的结构可调节性,制备的单金属钴MOF和聚丙烯腈之间具有好的分散性,二者共纺后使单金属钴MOF更均匀的分布在纳米纤维膜上,提高稳定性的同时,增加了吸附位点数量,有利于吸附;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879907A_ABST
    Figure CN122879907A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of nanofiber membrane, in particular to a single metal cobalt MOF-polyacrylonitrile electrospinning nanofiber membrane, a preparation method and application thereof, the single metal cobalt MOF is prepared first, then the single metal cobalt MOF and polyacrylonitrile are dissolved in N, N-dimethylformamide solution, and after stirring, a uniformly dispersed spinning solution is obtained, and a single metal cobalt MOF-polyacrylonitrile (PAN) electrospinning nanofiber membrane is obtained after electrospinning. After the combination of electrospinning technology and single metal cobalt MOF, MOFs can be dispersed and fixed in situ in the nanofiber membrane, which can improve the stability of the nanofiber membrane and effectively maintain the adsorption capacity of MOFs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanofiber membrane technology, specifically to a single-metal cobalt MOF-polyacrylonitrile electrospun nanofiber membrane, its preparation method, and its application. Background Technology

[0002] With the increasingly severe problem of particulate matter pollution, which can penetrate deep into the human respiratory, cardiovascular, and central nervous systems and induce various diseases, the combined effects of indoor and outdoor pollution sources further exacerbate the health exposure risks to the population. While traditional HEPA filters can achieve high particulate matter removal efficiency, they suffer from core drawbacks such as large filtration pressure drop and high energy consumption in HVAC systems. There is an urgent need to develop composite nanofiber filter media that combine high filtration efficiency with low air resistance.

[0003] Metal-organic frameworks (MOFs), synthesized from organic ligands and inorganic metal ions or metal clusters, possess advantages such as large surface area, high porosity, and good stability, and have been widely used in antibacterial applications, gas storage, adsorption separation, sensing, drug delivery for diagnosis and treatment, and photocatalysis. In recent years, the use of MOFs for filtering air pollutants has attracted widespread attention. Electrospinning is a simple and effective technique for preparing continuous fibers. Leveraging the inherent advantages of polymers, fiber composite membranes have been successfully prepared by electrospinning various powdered materials. Electrospun nanofiber membranes (ENFMs) consist of nanofibers with diameters ranging from tens to hundreds of nanometers. They possess advantages such as simple preparation, small thickness, large specific surface area, good thermal stability, high porosity, strong tunability, and easy recyclability, and are therefore considered ideal substrates for loading MOFs. Furthermore, through blending electrospinning technology, powdered MOFs can be dispersed and fixed in situ in ENFMs, which can effectively maintain the adsorption and catalytic capabilities of MOFs while improving their stability. Among the many polymers used to prepare electrospinned composite membranes, PAN is a matrix membrane with good electrochemical performance and thermal stability.

[0004] In view of the above-mentioned defects, the inventors of this invention have finally obtained this invention after a long period of research and practice. Summary of the Invention

[0005] The purpose of this invention is to solve the problem of how to develop composite nanofiber filter media that have both high filtration efficiency and low air resistance, and to provide a monometallic cobalt MOF-polyacrylonitrile electrospun nanofiber membrane, its preparation method and its application.

[0006] To achieve the above objectives, this invention discloses a method for preparing a single-metal cobalt MOF-polyacrylonitrile electrospun nanofiber membrane, comprising the following steps:

[0007] S1, dissolve polyacrylonitrile in N,N-dimethylformamide and stir to obtain a homogeneous polyacrylonitrile spinning solution;

[0008] S2, add cobalt MOF material to the polyacrylonitrile spinning solution obtained in step S1, stir and sonicate to obtain an electrospinning solution;

[0009] S3, electrospin the electrospinning solution obtained in step S2 to obtain a monometallic cobalt MOF-polyacrylonitrile electrospinned nanofiber membrane.

[0010] In step S1, the mass ratio of polyacrylonitrile to N,N-dimethylformamide is 0.9~1.4, and the mass fraction of polyacrylonitrile in the polyacrylonitrile spinning solution is 8~12wt%.

[0011] In step S1, the stirring temperature is 40℃ and the stirring time is 2 hours.

[0012] In step S2, the cobalt MOF material is ZIF-67. The preparation process of ZIF-67 is as follows: Co(NO)3·6H2O is fully dispersed in a methanol solution, then a methanol solution containing 2-methylimidazole is added, the mixture is magnetically stirred and aged, and then washed and dried to obtain ZIF-67.

[0013] The amount of Co(NO)3·6H2O used is 3.3g, which is dispersed in 45mL of methanol solution. The mass of 2-methylimidazole in the methanol solution containing 2-methylimidazole is 3.7g, and the volume of the methanol solution is 90mL.

[0014] The magnetic stirring time was 2 hours; the aging temperature was room temperature (25°C) and the aging time was 24 hours; the drying temperature was 60°C and the drying time was 12 hours.

[0015] In step S2, the amount of cobalt MOF material used is 0.1045g, the stirring temperature is 40℃, the stirring time is 3~6h, and the ultrasonic time is 10min.

[0016] In step S3, the electrospinning parameters are as follows: voltage is 22kV, injection speed is 0.0024mm / s, receiving distance is 17cm, and rotating mandrel speed is 200rpm.

[0017] The present invention also discloses a monometallic cobalt MOF-polyacrylonitrile electrospun nanofiber membrane prepared by the above preparation method and the application of this monometallic cobalt MOF-polyacrylonitrile electrospun nanofiber membrane in air filters.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0019] 1. This invention utilizes the large specific surface area, abundant metal active sites, and high structural tunability of metal-organic framework (MOF) materials to prepare a single metal cobalt MOF with good dispersibility with polyacrylonitrile. After co-spinning, the single metal cobalt MOF is more uniformly distributed on the nanofiber membrane, which improves stability and increases the number of adsorption sites, thus facilitating adsorption.

[0020] 2. Compared with nanofiber membranes prepared by in-situ growth, which are difficult to produce on a large scale, the MOF-polyacrylonitrile (PAN) nanofiber membrane prepared by blend electrospinning in this invention is easier to apply in actual production.

[0021] 3. In this invention, each nanofiber is interwoven with the others, making the monometallic cobalt MOF-polyacrylonitrile (PAN) electrospun nanofiber membrane very stable in actual use. It can be used in harsher environments and has broad application prospects. Attached Figure Description

[0022] Figure 1 X-ray diffraction patterns of ZIF-67, ZIF-67 / PAN-6%, ZIF-67 / PAN-9%, ZIF-67 / PAN-12%, and ZIF-67 / PAN-15% obtained in Examples 1-4 of this invention;

[0023] Figure 2 In the figures, (a) to (b) are scanning electron microscope (SEM) images of the PAN nanofiber membrane obtained in Comparative Example 1, (c) to (d) are SEM images of the ZIF-67 / PAN-9% nanofiber membrane obtained in Example 2, (e) to (f) are SEM images of the ZIF-67 / PAN-12% nanofiber membrane obtained in Example 3, (g) to (h) are SEM images of the ZIF-67 / PAN-15% nanofiber membrane obtained in Example 4, and (i) is the transmission spectrum and elemental distribution of the ZIF-67 / PAN-12% nanofiber membrane obtained in Example 3.

[0024] Figure 3 Thermogravimetric diagrams of ZIF-67, ZIF-67 / PAN-9%, ZIF-67 / PAN-12%, ZIF-67 / PAN-15% and PAN obtained in Examples 2, 3, 4 and Comparative Example 1 of the present invention are shown.

[0025] Figure 4 Fourier transform infrared spectra of ZIF-67, ZIF-67 / PAN-12% and PAN prepared in Example 3 and Comparative Example 1 of the present invention;

[0026] Figure 5In the figure, (a) is a graph of PM filtration efficiency of Comparative Example 1, Example 1, 2, 3 and 4 of the present invention, (b) is a graph of pressure drop and corresponding quality factor of Comparative Example 1, Example 1, 2, 3 and 4 of the present invention, and (c) is a graph of PM filtration effect of Comparative Example 1 and Example 3 of the present invention under different wind speeds.

[0027] Figure 6 In the diagram, (a) represents PMs from Examples 5, 6, 7, 8, 9, and 10 of this invention. 2.5 The filtration efficiency graph (b) shows the PM efficiency of Examples 5, 6, 7, 8, 9, and 10 of this invention. 10 The filtration efficiency graph (c) shows the pressure drop and corresponding quality factor graphs for Examples 5, 6, 7, 8, 9, and 10 of this invention.

[0028] Figure 7 This is a graph showing the PM filtration efficiency of ZIF-67 / PAN-12% obtained in Example 3 of the present invention within one month.

[0029] Figure 8 The images show the X-ray diffraction patterns of ZIF-67 / PAN-12% before and after filtration in Example 3 of this invention. Detailed Implementation

[0030] The above-mentioned and other technical features and advantages of the present invention will be described in more detail below with reference to the accompanying drawings.

[0031] Example 1

[0032] (1) Preparation of Co-MOF: 3.3 g Co(NO)3·6H2O was fully dispersed in 45 mL of methanol. Then, 90 mL of methanol containing 3.7 g 2-methylimidazole was rapidly added to the solution. The mixture was magnetically stirred for 2 hours, and then aged in an aging chamber at room temperature for 24 hours. After this aging period, a purple precipitate was formed, which was then washed six times with methanol by centrifugation. The obtained product was dried in a vacuum oven at 60 °C for 12 h to form ZIF-67 powder.

[0033] (2) Preparation of monometallic cobalt MOF-polyacrylonitrile (PAN) electrospun nanofiber membrane: First, 0.87 g of polyacrylonitrile (PAN) was dissolved in 7.83 g of DMF to prepare a 10 wt% PAN spinning solution, which was stirred at 40 °C for 2 h. Then, 0.0522 g of ZIF-67 was added to the homogeneous solution and stirred for 1.5 h, followed by sonication for 10 min, wherein the ratio of ZIF-67 to PAN was 6 wt%. The ZIF-67 / PAN electrospun solution was transferred to a 10 mL syringe and spun for 1.25 h. The ZIF-67 / PAN fibers were uniformly distributed on the rotating foil to form a filter membrane. The electrospinning parameters included: voltage 22 kV, injection speed 0.0024 mm / s, receiving distance 17 cm, and rotating mandrel speed 200 rpm. Finally, the obtained composite nanofiber membrane was vacuum dried at 60 °C for 12 h before use.

[0034] Example 2

[0035] (1) Preparation of Co-MOF: 3.3 g Co(NO)3·6H2O was fully dispersed in 45 mL of methanol. Then, 90 mL of methanol containing 3.7 g 2-methylimidazole was rapidly added to the solution. The mixture was magnetically stirred for 2 hours, and then aged in an aging chamber at room temperature for 24 hours. After this aging period, a purple precipitate was formed, which was then washed six times with methanol by centrifugation. The obtained product was dried in a vacuum oven at 60 °C for 12 h to form ZIF-67 powder.

[0036] (2) Preparation of monometallic cobalt MOF-polyacrylonitrile (PAN) electrospun nanofiber membrane: First, 0.87 g of polyacrylonitrile (PAN) was dissolved in 7.83 g of DMF to prepare a 10 wt% PAN spinning solution, which was stirred at 40 °C for 2 h. Then, 0.0783 g of ZIF-67 was added to the homogeneous solution and stirred for 1.5 h, followed by sonication for 10 min, wherein the ratio of ZIF-67 to PAN was 9 wt%. The ZIF-67 / PAN electrospun solution was transferred to a 10 mL syringe and spun for 1.25 h. The ZIF-67 / PAN fibers were uniformly distributed on the rotating foil to form a filter membrane. The electrospinning parameters included: voltage 22 kV, injection speed 0.0024 mm / s, receiving distance 17 cm, and rotating mandrel speed 200 rpm. Finally, the obtained composite nanofiber membrane was vacuum dried at 60 °C for 12 h before use.

[0037] Example 3

[0038] (1) Preparation of Co-MOF: 3.3 g Co(NO)3·6H2O was fully dispersed in 45 mL of methanol. Then, 90 mL of methanol containing 3.7 g 2-methylimidazole was rapidly added to the solution. The mixture was magnetically stirred for 2 hours, and then aged in an aging chamber at room temperature for 24 hours. After this aging period, a purple precipitate was formed, which was then washed six times with methanol by centrifugation. The obtained product was dried in a vacuum oven at 60 °C for 12 h to form ZIF-67 powder.

[0039] (2) Preparation of monometallic cobalt MOF-polyacrylonitrile (PAN) electrospun nanofiber membrane: First, 0.87 g of polyacrylonitrile (PAN) was dissolved in 7.83 g of DMF to prepare a 10 wt% PAN spinning solution, which was stirred at 40 °C for 2 h. Then, 0.1044 g of ZIF-67 was added to the homogeneous solution and stirred for 1.5 h, followed by sonication for 10 min, wherein the ratio of ZIF-67 to PAN was 12 wt%. The ZIF-67 / PAN electrospun solution was transferred to a 10 mL syringe and spun for 1.25 h. The ZIF-67 / PAN fibers were uniformly distributed on the rotating foil to form a filter membrane. The electrospinning parameters included: voltage 22 kV, injection speed 0.0024 mm / s, receiving distance 17 cm, and rotating mandrel speed 200 rpm. Finally, the obtained composite nanofiber membrane was vacuum dried at 60 °C for 12 h before use.

[0040] Example 4

[0041] (1) Preparation of Co-MOF: 3.3 g Co(NO)3·6H2O was fully dispersed in 45 mL of methanol. Then, 90 mL of methanol containing 3.7 g 2-methylimidazole was rapidly added to the solution. The mixture was magnetically stirred for 2 hours, and then aged in an aging chamber at room temperature for 24 hours. After this aging period, a purple precipitate was formed, which was then washed six times with methanol by centrifugation. The obtained product was dried in a vacuum oven at 60 °C for 12 h to form ZIF-67 powder.

[0042] (2) Preparation of monometallic cobalt MOF-polyacrylonitrile (PAN) electrospun nanofiber membrane: First, 0.87 g of polyacrylonitrile (PAN) was dissolved in 7.83 g of DMF to prepare a 10 wt% PAN spinning solution, which was stirred at 40 °C for 2 h. Then, 0.1305 g of ZIF-67 was added to the homogeneous solution and stirred for 1.5 h, followed by sonication for 10 min, wherein the ratio of ZIF-67 to PAN was 15 wt%. The ZIF-67 / PAN electrospun solution was transferred to a 10 mL syringe and spun for 1.25 h. The ZIF-67 / PAN fibers were uniformly distributed on the rotating foil to form a filter membrane. The electrospinning parameters included: voltage 22 kV, injection speed 0.0024 mm / s, receiving distance 17 cm, and rotating mandrel speed 200 rpm. Finally, the obtained composite nanofiber membrane was vacuum dried at 60 °C for 12 h before use.

[0043] Example 5

[0044] (1) Preparation of Co-MOF: 3.3 g Co(NO)3·6H2O was fully dispersed in 45 mL of methanol. Then, 90 mL of methanol containing 3.7 g 2-methylimidazole was rapidly added to the solution. The mixture was magnetically stirred for 2 hours, and then aged in an aging chamber at room temperature for 24 hours. After this aging period, a purple precipitate was formed, which was then washed six times with methanol by centrifugation. The obtained product was dried in a vacuum oven at 60 °C for 12 h to form ZIF-67 powder.

[0045] (2) Preparation of monometallic cobalt MOF-polyacrylonitrile (PAN) electrospun nanofiber membrane: First, 0.87 g of polyacrylonitrile (PAN) was dissolved in 7.83 g of DMF to prepare a 10 wt% PAN spinning solution, which was stirred at 40 °C for 2 h. Then, 0.1044 g of ZIF-67 was added to the homogeneous solution and stirred for 1.5 h, followed by sonication for 10 min, wherein the ratio of ZIF-67 to PAN was 12 wt%. The ZIF-67 / PAN electrospun solution was transferred to a 10 mL syringe and spun for 0.5 h. The ZIF-67 / PAN fibers were uniformly distributed on the rotating foil to form a filter membrane. The electrospinning parameters included: voltage 22 kV, injection speed 0.0024 mm / s, receiving distance 17 cm, and rotating mandrel speed 200 rpm. Finally, the obtained composite nanofiber membrane was vacuum dried at 60 °C for 12 h before use.

[0046] Example 6

[0047] The difference between this embodiment and embodiment 3 is that the spinning time in step (2) is changed to 0.75 hours, while other conditions are the same as in embodiment 3.

[0048] Example 7

[0049] The difference between this embodiment and embodiment 3 is that the spinning time in step (2) is changed to 1 hour, while other conditions are the same as in embodiment 3.

[0050] Example 8

[0051] The difference between this embodiment and embodiment 3 is that the spinning time in step (2) is changed to 1.5 hours, while other conditions are the same as in embodiment 3.

[0052] Example 9

[0053] The difference between this embodiment and embodiment 3 is that the spinning time in step (2) is changed to 1.75 hours, while other conditions are the same as in embodiment 3.

[0054] Example 10

[0055] The difference between this embodiment and embodiment 3 is that the spinning time in step (2) is changed to 2 hours, while other conditions are the same as in embodiment 3.

[0056] Example 11

[0057] The difference between this embodiment and embodiment 3 is that the concentration of the PAN spinning solution in step (1) is changed to an 8wt% solution, while other conditions are the same as in embodiment 3.

[0058] Example 12

[0059] The difference between this embodiment and embodiment 3 is that the concentration of the PAN spinning solution in step (1) is changed to a 12wt% solution, while other conditions are the same as in embodiment 3.

[0060] Comparative Example 1

[0061] Preparation of polyacrylonitrile (PAN) electrospun nanofiber membrane: First, 0.87 g of polyacrylonitrile (PAN) was dissolved in 7.83 g of DMF to prepare a 10 wt% PAN spinning solution, which was stirred at 40 °C for 2 h. The PAN electrospinning solution was transferred to a 10 mL syringe, and spinning was carried out for 1.25 h. PAN fibers were uniformly distributed on a rotating foil to form a filter membrane. The electrospinning parameters included: voltage: 22 kV, injection speed: 0.0024 mm / s, receiving distance: 17 cm, and spindle speed: 200 rpm. Finally, the obtained composite nanofiber membrane was vacuum dried at 60 °C for 12 h before use.

[0062] I. Application of Cobalt MOF-Polyacrylonitrile (PAN) Electrospun Nanofiber Membranes in PM Filtration:

[0063] The nanofiber membranes prepared in Examples 1-10 above were used for PM filtration testing. The specific experimental procedure was as follows: Circular filter samples with a diameter of 13 cm were cut, and the filtration performance of the nanofiber membranes was tested using an XZ.JF001 particulate matter full-efficiency testing platform. Particulate matter was generated using potassium chloride (KCl) in an aerosol generator. Under the action of an air compressor, an airflow with a certain velocity carried the aerosol particles into the testing platform, passing through an effective filtration area of ​​121 cm². 2 Electrospun nanofiber membranes were developed, and their filtration efficiency and pressure drop were measured. The quality factor (QF) was used to comprehensively evaluate the filtration performance of the nanofiber membranes. PM filtration experiments showed that when the spinning time was 1.25 hours and the ZIF-67 content was 104.4 mg, the PM filtration efficiency was 99.76%, the pressure drop was only 72 Pa, and the quality factor was as high as 0.724 Pa. -1 .

[0064] II. Characterization of ZIF-67 and ZIF-67 / PAN composite materials:

[0065] 1. XRD analysis:

[0066] Figure 1 The images show X-ray diffraction patterns of ZIF-67, ZIF-67 / PAN-6%, ZIF-67 / PAN-9%, ZIF-67 / PAN-12%, ZIF-67 / PAN-15%, and PAN obtained in Examples 1-4 and Comparative Example 1 of this invention. Figure 1 It can be seen that the peaks at 2θ of 16.8° and 29.4° belong to the (100) and (110) crystal planes of PAN (JCPDS: No. 25-1687). In addition, characteristic peaks of 7.3°, 10.4°, 12.7°, 16.5° and 18.1° of octahedral ZIF-67 (COD: No. 4118891) were also observed. These characteristic peaks have good refractive indices with the (100) and (110) crystal planes of PAN (JCPDS: No. 25-1687). The prepared heterostructure exhibits characteristic peaks of both PAN and ZIF-67. No impurity peaks were observed, ensuring the purity of ZIF-67.

[0067] 2. SEM testing:

[0068] Figure 2The images show scanning electron microscope (SEM) images of ZIF-67 / PAN-9%, ZIF-67 / PAN-12%, and ZIF-67 / PAN-15% prepared in Comparative Example 1 and Examples 2, 3, and 4 of this invention. The comparison reveals that with increasing ZIF-67 content, ZIF-67 particles significantly aggregate and deposit on the PAN fiber surface, with no free or amorphous substances observed, demonstrating the high mechanical stability of ZIF-67 / PAN. Furthermore, with increasing ZIF-67 loading, a significant change in the diameter of the nanofiber membrane was observed, becoming increasingly finer. This may be due to the increased conductivity of the spinning solution after the addition of ZIF-67; under the same voltage conditions, the polymer droplets are stretched into finer fibers by the enhanced electric field force, proving the successful preparation of ZIF-67 / PAN-12%. In addition, the EDS elemental diagram of ZIF-67 / PAN-12% shows that C, N, O, and Co elements are uniformly distributed and dispersed on the PAN surface.

[0069] 3. TG Analysis:

[0070] The thermal stability of the prepared ZIF-67, ZIF-67 / PAN-9%, ZIF-67 / PAN-12%, ZIF-67 / PAN-15%, and PAN was analyzed by thermogravimetric analysis (TG). Figure 3 The thermal stability of ZIF-67, pure PAN, and ZIF-67 / PAN nanofiber membranes was tested using TGA in an air atmosphere, and the results are as follows: Figure 3As shown, the thermal decomposition process of pure PAN mainly consists of three characteristic stages. In the range of room temperature to 300℃, the mass loss rate is 5%, primarily due to the evaporation of adsorbed water and residual solvents on the material surface. The second stage, at 300–470℃, involves significant chemical changes with a mass loss rate of 80%–90%, during which the PAN chains undergo dehydrogenation and thermal oxidative cracking. In the third stage, above 550℃, the material mass remains relatively stable, with a carbon residue rate of less than 5% and almost no solid residue. The thermal stability and thermal decomposition pathway of pure ZIF-67 differ fundamentally from that of pure PAN. Its mass loss mainly consists of two key stages. The first mass loss at approximately 150℃ is related to the evaporation of solvent molecules in the channels. Due to ligand oxidation and skeletal collapse, the second mass loss begins around 280℃, with a mass loss rate of 45%–55%. The TGA results for ZIF-67 combined with PAN show a similar trend to those for pure PAN, but with some subtle differences. First, the weight loss rate of the composite filter material in the first stage was slightly higher than that of pure PAN, mainly attributed to the porous adsorption characteristics of ZIF-67, which resulted in higher adsorption of solvent and moisture content. Second, the thermal decomposition temperature increased from 285℃ to 320℃. This is likely because the interaction between the ZIF-67 framework and the PAN polymer affected the PAN chain breakage. With the increase of the MOF loading ratio (from 3% to 15%), the maximum thermal decomposition temperature of the composite filter material gradually increased. Based on the weight loss at 800℃, the residual masses of ZIF-67, pure PAN, ZIF-67 / PAN-9%, ZIF-67 / PAN-12%, and ZIF-67 / PAN-15% were 30.22wt%, 0.74wt%, 2.56wt%, 3.12wt%, and 8.63wt%, respectively. However, the excessive incorporation of ZIF-67 (15wt%) caused particle aggregation in the precursor solution, hindering fiber formation during electrospinning. Therefore, the actual ZIF-67 doping amount in the membrane is slightly lower than the initial doping amount.

[0071] 4. ATR-FITR analysis:

[0072] like Figure 4 As shown, the ATR-FTIR spectrum of ZIF-67 / PAN-12% shows not only the absorption peak of PAN but also the characteristic peak of ZIF-67. The absorption peaks are caused by the contraction and bending vibrations of the imidazole ring. Specifically, the peak at 1577 cm⁻¹... -1 The nearby peaks are caused by the stretching vibrations of the C=N double bonds on the imidazole ring, while the peak at 1450 cm⁻¹ is... -1 The peak at 425 cm⁻¹ is due to the stretching vibration of the CH bond in 2-MI. Additionally, the peak at 425 cm⁻¹... -1 The nearby peaks are characteristic peaks generated by the stretching vibrations of Co-N. The results confirm that ZIF-67 was successfully loaded, consistent with the conclusions drawn from EDS analysis.

[0073] III. PM filtration test of monometallic cobalt MOF-polyacrylonitrile (PAN) electrospun nanofiber membrane:

[0074] 1. Effect of MOF content on PM filtration efficiency of ZIF-67 / PAN nanofiber membrane:

[0075] When the speed is set to 1.92m 3 When the electrospinning time is fixed at 1.25 h, the PM filtration efficiency increases with the MOF content and then remains stable. This is because PAN nanofibers, after MOF conversion, have a smaller pore structure, which can effectively filter particulate matter and improve filtration performance. However, when the MOF content reaches 15%, the filtration performance decreases, and the pressure drop increases sharply. This may be because, with the continuous increase of ZIF-67 mass fraction, particles interact through van der Waals forces, resulting in agglomeration on the fiber surface and a decrease in filtration efficiency. The pressure drop of ZIF-67 / PAN nanofiber membranes with different MOF contents is shown in the figure. Figure 5 As shown in (b). According to Figure 5 (b) The quality factor of nanofiber membranes of the same thickness also increased with increasing MOF content, reaching its highest value at 12% and then decreasing. The filtration efficiency and pressure drop of ZIF-67 / PAN-12% nanofiber membranes at different wind velocities were also measured. Figure 5 (c) indicates that the pressure drop increases with increasing wind speed, directly proportional to the airflow velocity, which conforms to Darcy's law. However, the filtration efficiency is inversely proportional to the airflow velocity. But because the blended ZIF-67 embedded in the nanofiber has a relatively stable structure, it can still achieve a PM filtration efficiency of over 97.12% at a high speed of 50 L / min.

[0076] 2. Effect of spinning time on PM filtration efficiency of ZIF-67 / PAN nanofiber membrane:

[0077] Figure 6 (a) and Figure 6 (b) Measurement results show that pure PAN film has a lower effect on PM2.5 levels. 2.5 and PM 10 The adsorption and filtration effects were poor. Correspondingly, the filtration efficiency of all membranes containing ZIF-67 particles exceeded 88.12%. From the EDS energy spectrum of ZIF-67 / PAN-12% (… Figure 2As shown in i), the content of Co, a characteristic element of ZIF-67, is 2% atomic fraction, and its elemental distribution indicates that ZIF-67 is uniformly dispersed in the nanofiber membrane. This gives the nanofiber membrane a relatively rough surface, increasing the specific surface area and contact points of the fibers, which facilitates effective airflow penetration, thereby reducing pressure drop and enhancing the electrostatic adsorption capacity of the fibers, thus improving PM filtration efficiency. With increasing spinning time, the filtration efficiency of the pure PAN membrane improved, but the maximum efficiency did not exceed 91.27%, while the prepared composite membrane maintained a filtration efficiency exceeding 99.45%. Generally, both the filtration efficiency and filtration pressure drop of fiber membranes increase with increasing spinning time; therefore, judging the filtration performance of fiber membranes solely by filtration efficiency is not comprehensive enough. Therefore, combining... Figure 6 (c) It can be seen that when the electrospinning time is 1.25h, the filtration efficiency of Z12 / P nanofiber membrane is 99.69% and the filtration pressure drop is 72Pa. At this time, the quality factor is the highest, which is 1.8 times that of pure PAN nanofiber membrane.

[0078] IV. Cyclic testing of monometallic cobalt MOF-polyacrylonitrile (PAN) electrospun nanofiber membranes:

[0079] Figure 7 The graph shows a one-month PM filtration test of the ZIF-67 / PAN-12% nanofiber membrane. As can be seen from the graph, the PM filtration performance of the nanofiber membrane did not decrease significantly after one month of PM filtration testing, indicating that it has excellent stability.

[0080] Figure 8 The image shows the XRD pattern of the ZIF-67 / PAN-12% nanofiber membrane after one month of PM filtration testing. As can be seen from the image, the crystallinity of ZIF-67 decreased significantly after one month of PM filtration testing, indicating that long-term filtration has certain damage to the nanofiber membrane.

[0081] The above description is merely a preferred embodiment of the present invention and is illustrative rather than restrictive. Those skilled in the art will understand that many changes, modifications, and even equivalents can be made within the spirit and scope defined by the claims of the present invention, all of which will fall within the protection scope of the present invention.

Claims

1. A method for preparing a single-metal cobalt MOF-polyacrylonitrile electrospun nanofiber membrane, characterized in that, Includes the following steps: S1, dissolve polyacrylonitrile in N,N-dimethylformamide and stir to obtain a homogeneous polyacrylonitrile spinning solution; S2, add cobalt MOF material to the polyacrylonitrile spinning solution obtained in step S1, stir and sonicate to obtain an electrospinning solution; S3, electrospin the electrospinning solution obtained in step S2 to obtain a monometallic cobalt MOF-polyacrylonitrile electrospinned nanofiber membrane.

2. The method for preparing a single-metal cobalt MOF-polyacrylonitrile electrospun nanofiber membrane as described in claim 1, characterized in that, In step S1, the mass ratio of polyacrylonitrile to N,N-dimethylformamide is 0.9~1.4, and the mass fraction of polyacrylonitrile in the polyacrylonitrile spinning solution is 8~12wt%.

3. The method for preparing a single-metal cobalt MOF-polyacrylonitrile electrospun nanofiber membrane as described in claim 1, characterized in that, In step S1, the stirring temperature is 40℃ and the stirring time is 2 hours.

4. The method for preparing a single-metal cobalt MOF-polyacrylonitrile electrospun nanofiber membrane as described in claim 1, characterized in that, In step S2, the cobalt MOF material is ZIF-67. The preparation process of ZIF-67 is as follows: Co(NO)3·6H2O is fully dispersed in a methanol solution, then a methanol solution containing 2-methylimidazole is added, the mixture is magnetically stirred and aged, and then washed and dried to obtain ZIF-67.

5. The method for preparing a single-metal cobalt MOF-polyacrylonitrile electrospun nanofiber membrane as described in claim 4, characterized in that, The amount of Co(NO)3·6H2O used is 3.3g, which is dispersed in 45mL of methanol solution. The mass of 2-methylimidazole in the methanol solution containing 2-methylimidazole is 3.7g, and the volume of the methanol solution is 90mL.

6. The method for preparing a single-metal cobalt MOF-polyacrylonitrile electrospun nanofiber membrane as described in claim 4, characterized in that, The magnetic stirring time was 2 hours; the aging temperature was room temperature (25°C) and the aging time was 24 hours; the drying temperature was 60°C and the drying time was 12 hours.

7. The method for preparing a single-metal cobalt MOF-polyacrylonitrile electrospun nanofiber membrane as described in claim 1, characterized in that, In step S2, the amount of cobalt MOF material used is 0.1045g, the stirring temperature is 40℃, the stirring time is 3~6h, and the ultrasonic time is 10min.

8. The method for preparing a single-metal cobalt MOF-polyacrylonitrile electrospun nanofiber membrane as described in claim 1, characterized in that, In step S3, the electrospinning parameters are as follows: voltage is 22kV, injection speed is 0.0024mm / s, receiving distance is 17cm, and rotating mandrel speed is 200rpm.

9. A monometallic cobalt MOF-polyacrylonitrile electrospun nanofiber membrane prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the monometallic cobalt MOF-polyacrylonitrile electrospun nanofiber membrane as described in claim 9 in an air filter.